THE EFFORTS TO IMPROVE THE SPEAKING COMPETENCE OF VIII GRADERS AT SMPN 10 PONTIANAK THROUGH PJBL - Andayani, Fuji (LPPM STBA Pontianak, 2019)
This classroom action research aimed at improving the English speaking competence of the students of grade VIII at SMPN 10 Pontianak through PjBL (Project-Based Learning). This was classroom action research using Kemmis and McTaggart model: planning, action, observation and reflection. The result showed, by implementing PjBL, all students reached the minimum standard score of 82, even more students scored above 82. In the interactions, the result of the students’ improvement was described from the frequency of their producing English based on the categories. In the 1st cycle, 19 out of 34 students were categorized as good category. There were 10 students who are categorized as average and 5 students who were classified into very good category. There was no student categorized as excellent category. In the 2nd cycle, 14 students out of 34 students were categorized as very good category and 20 students who were classified into good category. There was no more student who categorized as average. There was no student categorized as excellent category.This means that the students’ speaking competence has been improved through PjBL.